Ordered boron nitride thin film growth with reactive magnetron sputtering - Loh, Li Quan (2017)
Boron Nitride thin films were deposited on pieces of diced Si wafer using High-power Impulse Magnetron Sputtering (HIPIMS) with a pure boron target. The growth parameters of N2 gas flow ratio and substrate temperature were varied. The thin films were characterised using Fourier Transform Infrared spectroscopy (FTIR) to obtain the extent of vertical ordering of h-BN, indicated by the peak ratio R780/1380, and the cubic content, calculated by the ratio of the peak intensities, acBN. From our results, to obtain BN thin films of high thermal conductivities, the optimum N2 gas flow ratio could be 50%. When the N2 gas flow ratio was 25%, the optimum substrate temperature could be 600C. Moreover, the extent of vertical ordering remained low for all substrate temperatures when the N2 gas flow ratio was 25%. Detailed study can be undertaken on BN thin films growth using HIPIMS with a pure boron target to develop better processes to obtain BN thin films of superior properties.